CuO NANOPARTICLES: SYNTHESIS, CHARACTERIZATION AND THEIR BACTERICIDAL EFFICACY - D, Manyasree; Peddi, Kiran Mayi; R, Ravikumar (International Journal of Applied Pharmaceutics, 2017)
Objective: In the present study copper oxide (CuO) nanoparticles were synthesized and characterized. The antibacterial activity of CuO nanoparticles was carried out against Escherichia coli, Proteus vulgaris, Staphylococcus aureus and Streptococcus mutans. Methods: The synthesis was carried out by coprecipitation method using copper sulfate and sodium hydroxide as precursors. The synthesized copper oxide nanoparticles were characterized by using X-ray diffraction (XRD), Fourier transforms infrared spectroscopy (FT-IR), UV-vis spectroscopy and scanning electron microscope (SEM) with Energy Dispersive X-ray Analysis (EDX) techniques. Besides, this study determines the antibacterial activity and minimum inhibitory concentration (MIC) of CuO nanoparticles against gram-positive (Staphylococcus aureus and Streptococcus mutans) and gram-negative (E. coli and Proteus vulgaris) bacteria. Results: The average crystallite size of CuO nanoparticles was found to be 19 nm by X-ray diffraction. FT-IR spectrum exhibited vibrational modes at 432 cm-1, 511 cm-1 and 611 cm-1were assigned for Cu-O stretching vibration. According to UV-Vis spectrum, two bands were observed at 402 nm and 422 nm. ED's spectrum shows only elemental copper (Cu) and oxide (O) and no other elemental impurity was observed. The antimicrobial assay revealed that Proteus vulgaris showed a maximum zone of inhibition (37 mm) at 50 mg/ml concentration of CuO nanoparticles. Conclusion: In conclusion, copper oxide is a good antibacterial agent against both gram positive and gram-negative organisms.